Bioavailability & absorption of Iron and Anemia - Kapil, Radhika (Indian Journal of Community Health, 2017)
Humans derive iron from their everyday diet, predominantly from plant foods and the rest from foods of animal origin. Iron is found in food as either haem or non-haem iron. Haem iron, which is about up to 40 per cent of the iron in meat, poultry, and fish, is well absorbed. All the iron in plants (fruits, vegetables, grains, nuts) is in the form of non-haem iron and is relatively poorly absorbed. Non-haem iron contributes about 90-95 per cent of total daily iron in vegan diets. In western countries,the intake of haem iron from meat and meat products accounts for bulk of the dietary iron. The haem iron consumption is minimal in developing countries with majority obtaining non-haem iron from cereals, pulses, vegetables and fruits'. The diets is plagued by low iron content and poor absorption. Major sources of non-haem iron are plant foods. The iron is chemically diverse, ranging from simple iron oxides and salts to more complex organic chelates such as hydroxyphosphates in phytoferritin(1).